Control de acceso vehicular automatizado mediante técnicas de aprendizaje automático en la ESPAM MFL - Loor Morán, Diego Oswaldo (2023)
The objective of this curricular integration work was to develop a computer system that uses automatic learning techniques for vehicular access in sector 8 at ESPAM MFL, with the purpose of safeguarding the security of those who access it. For its development, the authors considered carrying it out through 7 stages, starting from image capture, image processing, extraction of regions of interest, digital storage management, development of the web module, development of the mobile module, general integration of the systems and finally experimental tests. Based on the results obtained from the tests performed, it was evidenced that the time taken by the system to process a vehicle for access to the sector is an average of 15 to 20 seconds with an effectiveness of 95% in terms of correctly recognized license plates, concluding that the system met the general objective and therefore it is recommended to implement it in other sectors of the institution.